EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN TEAMS GAMES TOURNAMENTS (TGT) DITINJAU DARI TINGKAT KECERDASAN EMOSIONAL TERHADAP PRESTASI BELAJAR DAN HUBUNGAN INTERPERSONAL SISWA KELAS VIII SMP NEGERI KABUPATEN SLEM - Hidayati, Fina Hanifa; Mardiyana, Mardiyana; Kusmayadi, Tri Atmojo (Jurnal Pembelajaran Matematika, 2014)
Abstract: The purposes of this study were to determine the effect of instructional models on studentâs mathematics achievement learning and interpersonal relationshipÂ viewed from the student emotional intelligence. The learning model compared were direct learning model, TAI and TGT Cooperative Learning Model. This study was a quasi-experimental study. The samples were 263 students: 88 students for experiment, 85 students for experiment 2, and 90 students for the controlled class,. The data were collected from mathematics achievement tests, a set of questionnaire of interpersonal relationship and emotional intelligence. The data were analysed using unbalanced two way MANOVA. Based on the research findings, it can concluded as follows. (1) Both learning achievement and interpersonal relationships of students treated by TGT are better than students treated with TAI and direct learning model while learning achievement and interpersonal relationships of students treated by TAI are better than students treated by direct learning model; (2) a. The best learning achievement is reached by students with high emotional intelligence which followed by those with moderate level and low emotional intelligence; b. The interpersonal relationships of students with moderate emotional intelligence are the same as those with low level, and students with high level are better than students with medium and low level emotional intelligence; (3) In TAI and direct models, learning achievement of the students of any level of emotional intelligence are the same. In TGT model, learning achievement of students with high level of emotional intelligence are the same as those with moderate level, also moderate and low level of emotional intelligence have same learning achievement, and high level emotional intelligence better than students with low level of emotional intelligence in learning achievement; In direct learning and TAI models the best interpersonal relationships is reached by students with high emotional intelligence which followed by those with medium level and low emotional intelligence. In TGT model, interpersonal relationships of students with high level of emotional intelligence are the same as those with moderate level, and both of them are better than students with low level of emotional intelligence; In the moderate level of emotional intelligence, learning achievement of students treated by TAI and direct learning model are the same while learning achievement of students treated by TGT model are better than those treated by direct model, and learning achievement of students treated by TGT and TAI are the same. In the low level of emotional intelligence, achievement of students treated by TAI, TGT, and direct learning are the same; At any level of emotional intelligence, interpersonal relationships of students treated by TGT are better than those treated by TAI and direct learning, and interpersonal relationships of students treated by TAI are better than those treated by direct instructional model.Keywords: TAI, TGT, Emotional Intelligence, Learning Achievement, Interpersonal Relationships.